1981
DOI: 10.2514/3.50996
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the Interaction of 10.6 pm Laser Radiation with Reinforced Plastics

Abstract: The objective of this work was to develop a phenomenological model of pulsed CO 2 laser interaction with reinforced composite materials. Experimental observation has shown that the multilayer composite material delaminates under pulsed CO 2 laser irradiation. This is a consequence of the energy storage mechanism arising out of a finite absorption depth to the laser radiation. A heat transfer model was developed to describe the observed delamination behavior of the composite materials. Good agreement was obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…[11][12][13][14][15][16][17][18] The new phenomena and effects in the interaction of strong laser radiation with materials include an in-depth understanding of the causes and process rules and exploring its possible applications in developing optical modulators, saturable absorbers, solar cells, supercapacitors, and other optical devices. [19][20][21][22][23][24] Studying nonlinear optics is vital to developing laser technology, spectroscopy, and material structure analysis. [25][26][27][28] Recently, nanosheets have shown new optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18] The new phenomena and effects in the interaction of strong laser radiation with materials include an in-depth understanding of the causes and process rules and exploring its possible applications in developing optical modulators, saturable absorbers, solar cells, supercapacitors, and other optical devices. [19][20][21][22][23][24] Studying nonlinear optics is vital to developing laser technology, spectroscopy, and material structure analysis. [25][26][27][28] Recently, nanosheets have shown new optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Research on anti-laser properties of various materials is significant in laser material processing and in developing laser protective materials. In general, thermo, force and radiation are the main detriments that take place when laser interacts with materials [1,2], especially for high-energy laser, which is claimed to be a crucial threat in modern and future combats. Lots of researches have shown that there are two main approaches to protect items from high-energy laser radiation.…”
Section: Introductionmentioning
confidence: 99%